2001
DOI: 10.1046/j.1432-1327.2001.2680041095.x
|View full text |Cite
|
Sign up to set email alerts
|

Epitope mapping for four monoclonal antibodies against human plasminogen activator inhibitor type‐1

Abstract: The inhibitory mechanism of serine proteinase inhibitors of the serpin family is based on their unique conformational flexibility. The formation of a stable proteinase-serpin complex implies insertion of the reactive centre loop of the serpin into the large central b-sheet A and a shift in the relative positions of two groups of secondary structure elements, the smaller one including a-helix F. In order to elucidate this mechanism, we have used phage-display and alanine scanning mutagenesis to map the epitopes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
49
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 61 publications
3
49
0
Order By: Relevance
“…Active PAI-1 circulates in the bloodstream as a high affinity complex with vitronectin (Vn) (38), a cell adhesive glycoprotein, which is present in plasma in micromolar concentrations (39,40), and stabilizes the active conformation of PAI-1 through a decrease in the rate of its spontaneous inactivation (41,42). Although Vn does not significantly affect the SI for the reactions of PAI-1 with uPA and tPA (43)(44)(45), under physiological pH it decreases the k lim for both enzymes and dramatically increases the rate of the reaction with activated protein C (46). On the other hand, the binding of Vn results in an increase in both the rate and SI for the reaction of PAI-1 with thrombin (43,47,48).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Active PAI-1 circulates in the bloodstream as a high affinity complex with vitronectin (Vn) (38), a cell adhesive glycoprotein, which is present in plasma in micromolar concentrations (39,40), and stabilizes the active conformation of PAI-1 through a decrease in the rate of its spontaneous inactivation (41,42). Although Vn does not significantly affect the SI for the reactions of PAI-1 with uPA and tPA (43)(44)(45), under physiological pH it decreases the k lim for both enzymes and dramatically increases the rate of the reaction with activated protein C (46). On the other hand, the binding of Vn results in an increase in both the rate and SI for the reaction of PAI-1 with thrombin (43,47,48).…”
mentioning
confidence: 99%
“…On the other hand, the binding of Vn results in an increase in both the rate and SI for the reaction of PAI-1 with thrombin (43,47,48). Moreover, Vn dramatically enhances the fraction of the substrate reaction between tPA or uPA and complexes of PAI-1 with mAbs (MA-55F4C12, mAb-2) directed against ␣HF (44,45,49). Therefore, the binding of Vn and anti-␣HF mAbs to PAI-1 affects steps of the serpin mechanism, which contribute to distribution between substrate and inhibitory reactions.…”
mentioning
confidence: 99%
“…Despite attempts to develop small inhibitors of PAI-1 (27)(28)(29)(30), anti-PAI-1 monoclonal antibodies (mAbs), which combine high affinity and specificity of interaction, are major established models for studying intermolecular PAI-1 inactivation. A number of mAbs inactivating PAI-1 have been selected and characterized, and their epitopes have been identified as well as several possible mechanisms affecting PAI-1 activity (31)(32)(33)(34)(35)(36)(37). Two mechanisms of PAI-1 inactivation have been confirmed directly thus far: (i) acceleration of the active-to-latent transformation of PAI-1 by MA-33B8 (38) and (ii) prevention of MichaelisMenten complex formation by mAbs MA-44E4, MA-42A2F6, and MA-56A7C10 (32,39).…”
mentioning
confidence: 99%
“…Example [22]: Wind and colleagues (Wind, et al, 2001) used phage-displayed peptides and selected alanine mutants (SAMs) of human plasminogen activator inhibitor-1 (PAI-1) to identify the epitopes of four previously identified murine mAbs: Mab2, Mab6, AD3780, and AD3783. PAI-1 is a serpin comprising 3 ß sheets and 9 α helices which inhibits tissue-type plasminogen activator (tPA) and urinary-type plasminogen activator (uPA).…”
Section: Mechanism Of Ab Blockage Of Pai-1 Actionmentioning
confidence: 99%
“…Rather, SAMs showed that R133, R135, and F136 are part of the Mab2 epitope. Based on the teaching of Jin and colleagues (Jin, et al, 1992), the structure of PAI-1, and the previous mapping, Wind et al (Wind, et al, 2001) picked 14 residues between 102 and 156 for SAM. The functional epitopes identified for AD3780 and AD3783 are essentially identical, involving residues Q102, R103, Q125, D127, E130, R133, F136, I137, and D140 (bold for EC 50 increases 100-fold, and underscore for EC 50 increases 10-fold, plain for EC 50 increases 3-fold).…”
Section: Mechanism Of Ab Blockage Of Pai-1 Actionmentioning
confidence: 99%